Impacts of the U.S.-China Trade Conflicts News on U.S. and Chinese Stock Returns - Shih-Yung, Chiu (The Economics and Finance Letters, 2021)
With the China’s emergence in the global economy, the United States has faced a widening trade deficit with China, which led to a very unbalanced trade relationship. Acrimonious differences concerning the “fairness” of the two sides’ industry subsidies triggered the U.S.-China trade conflict (trade war) through the action of both countries levying extreme unilateral tariffs. The trade war has affected both the values of the import and export goods produced by firms and also have caused investors to lose confidence, thus inducing economic the panic that is reflected in price fluctuations in related stock markets. That is, U.S. and China stock markets may be sensitive to media news on the trade war, as reports of policy announcements result in corrections to investors’ market expectations. Thus, this research aims to reveal whether media news’ coverage of the U.S.-China trade conflicts predicts the two countries’ daily stock returns. We find that US-China trade news could increase two-day-ahead stock return in China, whereas the same news would decrease four-day-ahead stock return in US. The opposite effects imply that U.S. investors react pessimistically to news in a free and open market economic system, while Chinese investors are more optimistic about the news in a socialist market economic system with beliefs in their more powerful government.